RNA-binding protein ZFP36/TTP protects against ferroptosis by regulating autophagy signaling pathway in hepatic stellate cells. Issue 8 (2nd August 2020) - Zhang, Zili; Guo, Mei; Li, Yujia; Shen, Min; Kong, Desong; Shao, Jiangjuan; Ding, Hai; Tan, Shanzhong; Chen, Anping; Zhang, Feng; Zheng, Shizhong
ABSTRACT: Ferroptosis is a recently discovered form of programmed cell death, but its regulatory mechanisms remain poorly understood. Here, we show that the RNA-binding protein ZFP36/TTP (ZFP36 ring finger protein) plays a crucial role in regulating ferroptosis in hepatic stellate cells (HSCs). Upon exposure to ferroptosis-inducing compounds, the ubiquitin ligase FBXW7/CDC4 (F-box and WD repeat domain containing 7) decreased ZFP36 protein expression by recognizing SFSGLPS motif. FBXW7 plasmid contributed to classical ferroptotic events, whereas ZFP36 plasmid impaired FBXW7 plasmid-induced HSC ferroptosis. Interestingly, ZFP36 plasmid inhibited macroautophagy/autophagy activation by destabilizing ATG16L1 (autophagy related 16 like 1) mRNA. ATG16L1 plasmid eliminated the inhibitory action of ZFP36 plasmid on ferroptosis, and FBXW7 plasmid enhanced the effect of ATG16L1 plasmid on autophagy. Importantly, ZFP36 plasmid promoted ATG16L1 mRNA decay via binding to the AU-rich elements (AREs) within the 3ʹ-untranslated region. The internal mutation of the ARE region abrogated the ZFP36-mediated ATG16L1 mRNA instability, and prevented ZFP36 plasmid-mediated ferroptosis resistance. In mice, treatment with erastin and sorafenib alleviated murine liver fibrosis by inducing HSC ferroptosis. HSC-specific overexpression of Zfp36 impaired erastin- or sorafenib-induced HSC ferroptosis. Noteworthy, we analyzed the effect of sorafenib on HSC ferroptosis in fibrotic patients with hepatocellular carcinoma receiving sorafenib monotherapy. Attractively, sorafenib monotherapy led to ZFP36 downregulation, ferritinophagy activation, and ferroptosis induction in human HSCs. Overall, these results revealed novel molecular mechanisms and signaling pathways of ferroptosis, and also identified ZFP36-autophagy-dependent ferroptosis as a potential target for the treatment of liver fibrosis. Abbreviations: ARE: AU-rich elements; ATG: autophagy related; BECN1: beclin 1; CHX: cycloheximide; COL1A1: collagen type I alpha 1 chain; ELAVL1/HuR: ELAV like RNA binding protein 1; FBXW7/CDC4: F-box and WD repeat domain containing 7; FN1: fibronectin 1; FTH1: ferritin heavy chain 1; GPX4/PHGPx: glutathione peroxidase 4; GSH: glutathione; HCC: hepatocellular carcinoma; HSC: hepatic stellate cell; LSEC: liver sinusoidal endothelial cell; MAP1LC3A: microtubule associated protein 1 light chain 3 alpha; MDA: malondialdehyde; NCOA4: nuclear receptor coactivator 4; PTGS2/COX2: prostaglandin-endoperoxide synthase 2; RBP: RNA-binding protein; ROS: reactive oxygen species; SLC7A11/xCT: solute carrier family 7 member 11; SQSTM1/p62: sequestosome 1; TNF: tumor necrosis factor; TP53/p53: tumor protein p53; UTR: untranslated region; ZFP36/TTP: ZFP36 ring finger protein